Randomized comparative study between short duration (4 hour) vs. 24 hour post-partum magnesium sulphate therapy in severe preeclampsia - Sahu, Latika; Yadav, Preeti; Tempe, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective: To assess the safety and efficacy of shorter duration of magnesium sulphate therapy given till 4 hours after delivery as compared to the standard duration of 24 hours postpartum therapy, given to prevent eclampsia in patients with severe preeclampsia. Methods: A prospective randomized controlled study of magnesium sulphate therapy in women with severe preeclampsia was conducted with 50 patients each in control and study group. The control group received 24 hours of postpartum magnesium sulphate therapy and the study group received for 4 hours or one intramuscular dose in postpartum period. Chi square and unpaired “t” test were used for statistical analysis of data; a probability value of <0.05 was considered statistically significant. Results: There was no statistically significant difference in demographic data, disease severity, maternal and perinatal outcome. The need for IV anti-hypertensive postpartum was significantly higher in study group (12% vs. 0%, P=0.03). No patient developed eclampsia or required reinitiation of therapy. At the end of therapy serum magnesium levels were significantly lower in the study group. Conclusions: In patients with severe preeclampsia shorter duration (4 hours or one dose) of postpartum magnesium sulphate therapy, is as effective as the standard 24 hours of postpartum therapy.